The Role of Motor Representation in Enactment Effect of Action Memory - Zhang, Xinyuan; Assumpcao, Leonardo; Wang, Lijuan (Experimental psychology, 2023)
Noun-verb phrases are more efficiently remembered when they are enacted during learning than when they are only verbally studied, a phenomenon known as the . While studies have debated whether motor information is key to this effect, our study explores whether the organization of motor information can support the enactment effect. We used the retrieval-practice paradigm to induce retrieval-induced forgetting (RIF). In Experiment 1, we found an RIF effect of categorization into physical motor properties (e.g., rotation-motor category), which was significantly stronger during enactment learning. In Experiment 2, we also found an RIF effect of categorization into physical motor properties with additional imagery features (e.g., the hand-physical and round-object category), but there was no significant difference between enactment learning and verbal learning. These findings suggest that motor information is fundamental to the enactment effect, but it is not primarily assimilated, even in the presence of various types of information, in the processing of action memory. We discuss these findings in the context of multimodal theory and episodic integration theory.